Analisis Kepuasan Pengguna Sistem Informasi Manajemen Rumah Sakit Pelni dengan Metode SERVQUAL (Service Quality) - Wafi Hidayat Ahadi; I Ketut Sudaryana (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
This study aims to analyze user satisfaction with the Hospital Management Information System (SIMRS) implemented at Pelni Hospital using the SERVQUAL (Service Quality) method. The SERVQUAL method is used to measure Service Quality based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The research was conducted by distributing questionnaires to 31 respondents, including patients, medical staff, and administrative staff who actively use SIMRS. The results indicate that, overall, the quality of SIMRS services at Pelni Hospital is categorized as "Good" across all dimensions measured. The reliability dimension scored the highest (4.13), indicating that the system is reliable in providing services as promised. The assurance (4.06) and empathy (3.94) dimensions also received good scores, indicating that users feel safe and well-attended while using the system. However, the responsiveness (3.77) and tangibles (3.87) dimensions showed areas for improvement, such as the speed of response to user requests and improvements in the system's physical appearance, which can affect user comfort. The conclusion of this study is that SIMRS at Pelni Hospital provides adequate and satisfactory services, but improvements in the responsiveness and tangibles aspects are necessary to enhance overall user satisfaction.